Does causality between geopolitical risk, tourism and economic growth matter? Evidence from Turkey - Saint Akadiri, Seyi; Eluwole, Kayode Kolawole; Akadiri, Ada Chigozie; Avci, Turgay (Elsevier, 2020)
In recent times, the Arab Spring has seen most tourism-dependent economies such as Turkey experienced an unprecedented wave of political unrest which has impacted the outlook of the tourism industry significantly. To this effect, this study uses the modified version of the Granger causality approach advanced by Toda and Yamamoto (1995) to examine the direction of causality among the newly introduced geopolitical risk index, tourism and economic growth in the case of Turkey. To the best of our knowledge, this study is the first to examine the interrelationship between these variables in a multivariate causality study using quarterly frequency data 1985Q1-2017Q4. Empirical results indicate a unidirectional causality running from geopolitical risk index to economic growth and from geopolitical risk index to tourism. Finding also show that a one standard deviation shock to geopolitical risk has a noticeable negative impact on tourism and economic growth both in the short- and long-run.
Keywords: Geopolitical risk; Tourism; Economic growth; Time series; Turkey